Cosmetic

KR1020260132644APending Publication Date: 2026-09-02SHISEIDO CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020267027693
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-08-21
Filing Date
2020-08-19
Publication Date
2026-09-02

Smart Images

  • Figure P1020267027693_ABST
    Figure P1020267027693_ABST
Patent Text Reader

Abstract

A cosmetic product containing hyaluronic acid particles is provided that can maintain excellent moisturizing properties non-invasively over a long period of time. The cosmetic composition of the present disclosure comprises an aqueous medium and hyaluronic acid particles dispersed in the aqueous medium, and furthermore, the average particle diameter of the hyaluronic acid particles is 200 nm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a cosmetic composition for moisturizing. Background Technology

[0002] To moisturize the skin, hyaluronic acid with moisturizing properties is used in fields such as cosmetics.

[0003] Patent Document 1 discloses a cosmetic composition comprising hyaluronic acid-supported nanoparticles having hyaluronic acid supported on at least one of the interior or surface of nanoparticles formed from any one of polylactic acid, polyglycolic acid, and lactic acid-glycolic acid copolymer.

[0004] Patent document 2 discloses a topical skin preparation comprising (A) hyaluronic acid and (B) a cationic compound, and a composite nanoparticle having a particle size of 100 nm or less. Prior art literature

[0005] Patent Document 1: Japanese Patent Publication No. 2010-150151 Patent Document 2: International Publication No. 2018 / 182003 The problem to be solved

[0006] The stratum corneum, located at the outermost layer of the skin, functions as a barrier to prevent the intrusion of foreign substances from the outside environment; consequently, it has the property of making it difficult for active ingredients applied to the skin to reach the interior. For this reason, simply applying hyaluronic acid to the skin tends to limit its moisturizing effect to the surface, resulting in only short-term hydration. Consequently, to improve skin wrinkles and other issues, it was necessary to apply hyaluronic acid frequently and continuously over a long period.

[0007] For example, injecting hyaluronic acid into the skin using a syringe improves the duration of the moisturizing effect compared to topical application, but this method has the problem of causing pain due to the invasiveness of the injection.

[0008] Nanometer-order particles containing hyaluronic acid, as described in Patent Documents 1 and 2, can penetrate into the interior of the skin beyond the stratum corneum. However, since the hyaluronic acid content in the particles described in Patent Document 1 is low at about 3 mass%, and the hyaluronic acid content in the particles described in Patent Document 2 also remains at 50 mass% or less, there were cases where sufficient moisturizing properties could not be secured.

[0009] Accordingly, the subject of the present disclosure is to provide a cosmetic composition containing hyaluronic acid particles capable of maintaining excellent moisturizing properties non-invasively over a long period of time. means of solving the problem

[0010] <Mode 1>

[0011] A cosmetic composition comprising an aqueous medium and hyaluronic acid particles dispersed in the aqueous medium, wherein the average particle diameter of the hyaluronic acid particles is 200 nm or less.

[0012] <Mode 2>

[0013] A cosmetic composition described in Embodiment 1, wherein the weight average molecular weight of the hyaluronic acid is 10,000,000 or less.

[0014] <Mode 3>

[0015] A cosmetic composition described in Embodiment 1 or 2 comprising at least one salt selected from inorganic salts and organic acid salts.

[0016] <Mode 4>

[0017] A cosmetic composition described in Embodiment 3, wherein the ionic strength of the above salt is 0.01 or higher.

[0018] <Mode 5>

[0019] A cosmetic composition described in any one of embodiments 1 to 4, wherein the content of the hyaluronic acid particles is 0.005 mass% or more.

[0020] <Mode 6>

[0021] A cosmetic composition described in any one of embodiments 1 to 5, wherein the content of an ionic compound, a glycol, ethanol, and urea is 15 mass% or less, each.

[0022] <Mode 7>

[0023] A cosmetic product described in any one of embodiments 1 to 6, which is applied to the skin.

[0024] <Mode 8>

[0025] A method for preparing a cosmetic composition as described in any one of embodiments 1 to 7, wherein a salt is mixed with water or a buffer solution, and then hyaluronic acid is further mixed to prepare hyaluronic acid particles.

[0026] <Mode 9>

[0027] A method for preparing a cosmetic composition as described in any one of embodiments 1 to 7, wherein hyaluronic acid is dissolved by mixing it with water or a buffer solution, and then a salt is further mixed to prepare hyaluronic acid particles. Effects of the invention

[0028] According to the present disclosure, a cosmetic composition containing hyaluronic acid particles can be provided that can maintain excellent moisturizing properties non-invasively over a long period of time. Brief explanation of the drawing

[0029] Figure 1 is a graph regarding the Z average particle diameter and ionic strength of hyaluronic acid particles prepared using sodium chloride. Figure 2 is a graph regarding the Z average particle diameter and ionic strength of hyaluronic acid particles in compositions of each hyaluronic acid concentration prepared using sodium chloride. Figure 3 is a graph regarding the Z average particle diameter and ionic strength of hyaluronic acid particles in compositions of 0.4 mass% and 0.5 mass% hyaluronic acid concentrations prepared using sodium chloride. Figure 4 is a graph regarding the Z average particle diameter and moisturizing performance of hyaluronic acid particles. Figure 5 is a graph regarding the Z average particle diameter and ionic strength of hyaluronic acid particles prepared using citric acid buffer. Figure 6 is a graph regarding the Z average particle diameter of hyaluronic acid particles according to the addition of elements. Specific details for implementing the invention

[0030] The embodiments of the present disclosure are described in detail below. The present disclosure is not limited to the embodiments described below and may be implemented with various modifications within the scope of the spirit of the invention.

[0031] The cosmetic composition of the present disclosure comprises an aqueous medium and hyaluronic acid particles dispersed in the aqueous medium, and furthermore, the average particle diameter of the hyaluronic acid particles is 200 nm or less.

[0032] Although not limited by principle, the principle of action of the cosmetic composition containing hyaluronic acid particles of the present disclosure, which can maintain excellent moisturizing properties non-invasively over a long period of time, and the principle of action of the composition that can prepare hyaluronic acid particles with an average particle diameter of 200 nm or less that contain a high amount of hyaluronic acid components, are as follows.

[0033] Hyaluronic acid particles of 200 nm or less, particularly 100 nm or less, are prone to non-invasively penetrating the interior of the skin through the stratum corneum or pores, but particles of this size cannot penetrate the interior of the skin indefinitely, and it is thought that the amount of particle penetration is limited to some extent.

[0034] For example, the composite nanoparticles described in Patent Document 2 have a hyaluronic acid content of 50 mass% or less, whereas the hyaluronic acid particles of the present disclosure contain hyaluronic acid in a ratio exceeding 50 mass%. As a result, for example, when the particle diameter of the composite nanoparticles described in Patent Document 2 and the particle diameter of the hyaluronic acid particles of the present disclosure are the same, and the number of particles penetrating into the skin is the same, it is believed that the hyaluronic acid particles of the present disclosure have a higher ratio of hyaluronic acid content in the particles, and thus the moisturizing effect and its persistence within the skin can be improved.

[0035] Furthermore, generally, skin exposed to dryness loses moisture unwittingly, resulting in a state where it cannot maintain the moisture level on the skin surface. When the moisture on the skin surface is insufficient, the skin is unable to effectively produce its own moisturizing components (Natural Moisturizing Factors (NMF)). Consequently, the barrier function and moisturizing function on the skin surface deteriorate, making the skin more susceptible to damage. It is believed that this loss of moisture leads to wrinkles and skin roughness. The cosmetic composition disclosed herein is believed to be able to improve skin problems such as wrinkles because it allows a hyaluronic acid component, which functions as a moisturizer, to penetrate deep into the skin, thereby maintaining the moisture level near the inner surface of the skin for an extended period.

[0036] Hyaluronic acid generally has a negative charge due to the presence of carboxyl groups. Due to electrostatic repulsion based on this negative charge, hyaluronic acid molecules tend to diffuse into thread-like shapes, making it difficult to form particles. For this reason, in order to form hyaluronic acid molecules into particles, particularly into particles of 200 nm or less, a nanometer-order supporting material capable of supporting hyaluronic acid molecules was required, as described in Patent Documents 1 and 2, and thus, a limit was imposed on the content ratio of hyaluronic acid in the particles.

[0037] The inventors focused on the electrostatic repulsion that exerts a filament-like effect on hyaluronic acid molecules and the hydrogen bonding based on hydroxyl groups in hyaluronic acid that exerts an attractive effect. By utilizing the electrostatic shielding effect of an electrolyte such as sodium chloride, the negative charge of hyaluronic acid is outwardly neutralized, and by making hydrogen bonding dominant, the diffusion of hyaluronic acid molecules is suppressed, thereby enabling the hyaluronic acid molecules to be micronized to the nanometer order even when used alone. As a result, since the hyaluronic acid particles of the present disclosure can be prepared without using the support material described above, it became theoretically possible to make the hyaluronic acid content ratio in the particles 100 mass%.

[0038] Furthermore, even if electrolytes such as sodium chloride are present in the aqueous solution of hyaluronic acid, if it contains components that adversely affect hydrogen bonding or the apparent neutralization of negative charges, such as urea or ionic surfactants described later, it may be difficult to obtain the effect of inhibiting the diffusion of hyaluronic acid molecules and / or the effect of attracting hyaluronic acid molecules.

[0039] In addition, the hyaluronic acid particles of the present disclosure can maintain their particle shape in a cosmetic composition without the use of a crosslinking agent. This is believed to be the result of hydrogen bonding that exerts an intramolecular and / or intermolecular attractive action of the hyaluronic acid molecules.

[0040] Cosmetics containing hyaluronic acid particles

[0041] The cosmetic composition of the present disclosure comprises an aqueous medium and hyaluronic acid particles dispersed in the aqueous medium.

[0042] Hyaluronic acid particles

[0043] The penetration of hyaluronic acid particles into the skin varies by individual and may differ depending on the condition of the stratum corneum, the number or size of pores, etc., but it is known that if the average particle diameter is 200 nm or less, the particles can penetrate most of the skin. From the perspective of penetration into the skin and ease of preparing the particles, the average particle diameter of the hyaluronic acid particles can be, for example, 150 nm or less, 120 nm or less, or 100 nm or less, and can also be 10 nm or more, 30 nm or more, or 50 nm or more. Here, the average particle diameter refers to the Z average particle diameter of the hyaluronic acid particles optically measured by dynamic light scattering when the particle shape of the hyaluronic acid particles is assumed to be spherical. These average particle diameters can be measured, for example, using a Zetasizer (manufactured by Malvern Panalytical Co., Ltd.) or a dynamic light scattering photometer DLS-8000 (manufactured by Otsuka Denshi Co., Ltd.). These measuring devices can be appropriately selected based on the overlap concentration of each hyaluronic acid. For example, if the overlap concentration is less than 100%, the dynamic light scattering photometer DLS-8000 can be used, and if the overlap concentration is greater than 100%, the Zetasizer can be used. The overlap concentration can be calculated, for example, by the fluorescence recovery method after confocal fading (Confocal-FRAP).

[0044] The hyaluronic acid particles of the present disclosure are thought to exhibit a filamentous, ball-like shape in which hyaluronic acid molecules are intertwined and aggregated. Since such particles can be prepared without using the aforementioned supporting material, the hyaluronic acid content in the particles can theoretically be 100 mass%. That is, the hyaluronic acid particles of the present disclosure can be composed solely of hyaluronic acid molecules as a polymer component.

[0045] However, the hyaluronic acid particles of the present disclosure may contain other polymer components other than hyaluronic acid, provided that no problems arise regarding the average particle diameter, moisturizing performance, etc. As for the content ratio of other polymer components, with respect to the total amount of polymer contained in the hyaluronic acid particles, for example, 20 mass% or less, 10 mass% or less, 5 mass% or less, 3 mass% or less, or 1 mass% or less. That is, in the present disclosure, "hyaluronic acid particles" are intended to be particles containing a high amount of hyaluronic acid components in this manner, and particles having a ratio of hyaluronic acid components of 50 mass% or less, as described in Patent Documents 1 and 2, are not included. Here, the content ratio of hyaluronic acid in the hyaluronic acid particles can be measured, for example, using an ultraviolet-visible spectrophotometer (V-530, manufactured by Nihon Bunko Co., Ltd., measurement wavelength 270 nm).

[0046] As for the content of hyaluronic acid particles in the cosmetic composition, for example, from the perspective of moisturizing properties, cost, etc., it can be 0.005 mass% or more, 0.01 mass% or more, 0.05 mass% or more, 0.10 mass% or more, 0.15 mass% or more, 0.20 mass% or more, or 0.25 mass% or more with respect to the total amount of the cosmetic composition, and can also be 1.0 mass% or less, 0.80 mass% or less, 0.60 mass% or less, 0.50 mass% or less, or 0.45 mass% or less. As described above, the cosmetic composition of the present disclosure has a high hyaluronic acid content ratio and also contains hyaluronic acid particles with an average particle diameter of 200 nm or less that are easy to penetrate the skin non-invasively, so it can exhibit a sufficient moisturizing effect even if the content of hyaluronic acid particles in the cosmetic composition is relatively low.

[0047] (Hyaluronic acid)

[0048] There are no particular restrictions on the hyaluronic acid that can constitute hyaluronic acid particles. Generally, hyaluronic acid refers to a linear polymer in which N-acetyl-D-glucosamine residues and D-glucuronic acid residues are alternately linked, and such hyaluronic acid can be obtained, for example, by isolation extraction from chicken cocoons or other animal tissues, or by fermentation using microorganisms such as Streptococcus.

[0049] Hyaluronic acid may be a derivative thereof, for example, as a derivative of hyaluronic acid, metal salts of hyaluronic acid such as sodium hyaluronate, potassium hyaluronate, magnesium hyaluronate, calcium hyaluronate, and aluminum hyaluronate, or hyaluronic acid derivatives obtained by etherifying, esterifying, amidating, acetylating, acetalizing, or ketalizing the hydroxyl group, carboxyl group, etc. of hyaluronic acid may be used. Here, the concept of "hyaluronic acid" in the present disclosure may include hyaluronic acid and its derivatives.

[0050] There is no particular limit on the weight-average molecular weight of hyaluronic acid, and for example, it can be 10,000,000 or less. Generally, it is believed that hyaluronic acid with a relatively low molecular weight of less than 500 weight-average molecular weight is easy to penetrate the skin even without being micronized. However, since such low molecular weight hyaluronic acid is difficult to remain inside the skin and its moisture retention performance is inferior to that of high molecular weight hyaluronic acid, it may be difficult to sustain the moisturizing effect inside the skin for a long period of time. On the other hand, the hyaluronic acid particles of the present disclosure can be prepared using high molecular weight hyaluronic acid, and since such hyaluronic acid can be highly contained within the particles, the resulting hyaluronic acid particles are easy to remain inside the skin and can sustain the moisturizing effect inside the skin for a long period of time. From the perspective of moisture retention performance within the skin and ease of preparing particles, the weight-average molecular weight of hyaluronic acid can be, for example, 500 or more, 1,000 or more, 5,000 or more, 10,000 or more, 50,000 or more, 100,000 or more, 300,000 or more, 500,000 or more, 800,000 or more, or 1,000,000 or more, and can also be 10,000,000 or less, 8,000,000 or less, 5,000,000 or less, 3,000,000 or less, 2,000,000 or less, or 1,500,000 or less. Here, the weight-average molecular weight refers to the weight-average molecular weight in polystyrene equivalents in gel permeation chromatography measurements.

[0051] Hyaluronic acid may be used as hyaluronic acid and its derivatives alone or in combination of two or more types. In addition, the molecular weights of the hyaluronic acid and its derivatives used may be the same or different.

[0052] Commercially available hyaluronic acid may be used. Examples of commercially available hyaluronic acid include hyaluronic acid HA-LQ (manufactured by Qewpie Co., Ltd.), hyaluronic acid FCH (manufactured by Kikkoman Biochemipa Co., Ltd.), and sodium biohyaluronate HA12N (manufactured by Shiseido Co., Ltd.).

[0053] Mercury Media

[0054] There are no specific restrictions on the aqueous medium, and aqueous media used in cosmetics, quasi-drugs, etc. may be used. For example, ion-exchanged water, distilled water, ultrapure water, tap water, buffer solution, etc. may be used.

[0055] Examples of buffer solutions include citric acid buffer, lactic acid buffer, phosphate buffer, acetic acid buffer, tartaric acid buffer, boric acid buffer, and Tris buffer. Citric acid buffer, lactic acid buffer, and phosphate buffer are preferred in terms of high buffering capacity, and citric acid buffer is more preferred.

[0056] The pH of the buffer solution can be 7.0 or lower, 6.8 or lower, or 6.5 or lower. The lower limit of the pH of the buffer solution is not particularly limited, but, for example, from the perspective of skin irritation, it is preferable to have a value of 4.5 or higher, 5.5 or higher, or 6.0 or higher.

[0057] <salt>

[0058] Since the cosmetic composition of the present disclosure uses a salt when preparing hyaluronic acid particles, the cosmetic composition may contain a salt. There are no particular limitations on the salt that may be included in the cosmetic composition, as long as it is a salt capable of visibly neutralizing the negative charge of hyaluronic acid. Examples of such salts include at least one salt selected from inorganic salts and organic acid salts. When considering use as a cosmetic composition, it is preferable that the salt among inorganic salts and organic acid salts is less likely to have an adverse effect on the skin. Here, "inorganic salt" refers to a salt composed solely of inorganic components, and can be rephrased as a salt composed of ions generated from inorganic acids and inorganic bases. Furthermore, "organic acid salt" refers to a salt formed by the combination of an organic acid and a metal ion. Additionally, salts generally exist in the cosmetic composition in the form of ions derived from the salt. Therefore, in the present disclosure, for example, "a cosmetic composition containing a salt" is intended to mean that the salt is included in such an ion form. In addition, ionic surfactants are not included in the “salt” of the present disclosure.

[0059] Examples of inorganic salts include sodium nitrate, sodium sulfate, sodium chloride, potassium nitrate, potassium sulfate, potassium chloride, calcium nitrate, calcium sulfate, calcium chloride, magnesium nitrate, magnesium sulfate, magnesium chloride, aluminum nitrate, aluminum sulfate, aluminum chloride, etc. These salts may be used alone or in combination of two or more types.

[0060] Examples of organic acid salts include citrate, acetate, lactate, tartrate, succinate, malate, glycolate, salicylate, pyrrolidone carboxylate, etc. Specifically, examples include salts formed by combining organic acids such as citric acid, acetic acid, lactic acid, tartaric acid, succinic acid, malic acid, glycolic acid, salicylic acid, and pyrrolidone carboxylic acid with metal ions such as sodium ions, potassium ions, calcium ions, magnesium ions, and aluminum ions. These salts may be used individually or in combination of two or more types.

[0061] The amount of salt incorporated in the cosmetic composition can be defined by the ionic strength of the salt. The ionic strength of the salt may be, for example, 0.01 or more, 0.03 or more, or 0.05 or more. There is no specific limit on the upper limit of the ionic strength, but it may be, for example, 4.0 or less, 3.0 or less, 2.0 or less, or 1.0 or less. Here, for example, when a cosmetic composition is prepared by adding a salt to a buffer solution, the ionic strength is calculated based on all salt components, including the salt component contained in the buffer solution itself and the salt component separately added to the buffer solution.

[0062] <Arbitrary Component>

[0063] The cosmetic composition of the present disclosure may appropriately combine various ingredients within a range that does not affect the effects of the present invention. Examples of such ingredients include skin nutrients, vitamins, water-soluble agents applicable to pharmaceuticals, quasi-pharmaceuticals, cosmetics, etc., ultraviolet absorbers, antioxidants, preservatives, antioxidant agents, thickeners, pigments, dyes, colorants, fragrances, etc. Any of these ingredients may be used alone or in combination of two or more.

[0064] The hyaluronic acid particles of the present disclosure are prepared by seemingly neutralizing the negative charge of hyaluronic acid and giving dominance to intramolecular or intermolecular hydrogen bonding of hyaluronic acid, as described above. Accordingly, for example, additives such as those that seem to neutralize the negative charge of hyaluronic acid and / or inhibit hydrogen bonding to make the average particle diameter of the hyaluronic acid particles greater than 200 nm, or additives such as those that bind to the negative charge of hyaluronic acid and / or hydrogen bond with hyaluronic acid to make the average particle diameter of the hyaluronic acid particles greater than 200 nm, may be included in the range of 15 mass% or less, 10 mass% or less, 5 mass% or less, 1 mass% or less, 0.5 mass% or less, or 0.1 mass% or less, respectively, with respect to the total amount of the cosmetic composition, but it is preferable that these additives are not included.

[0065] Examples of such additives include ionic compounds such as ionic surfactants, glycols such as 1,3-butylene glycol, dipropylene glycol, and isoprene glycol, ethanol, and urea. In particular, cationic surfactants or compounds may electrostatically bond with hyaluronic acid, which has a negative charge, and thus increase the particle diameter; glycols and ethanol may also hydrogen bond with hyaluronic acid and increase the particle diameter. Additionally, urea may increase the particle diameter because it exhibits the action of breaking hydrogen bonds, which are important for particle formation.

[0066] Method of preparing cosmetics

[0067] The cosmetic composition of the present disclosure can be prepared, for example, by using the following method.

[0068] A solution can be prepared by combining a salt with water or a buffer solution, adding hyaluronic acid to this solution, and dissolving the hyaluronic acid while stirring to form hyaluronic acid particles, thereby preparing a cosmetic product.

[0069] Alternatively, a cosmetic product can be prepared by combining hyaluronic acid with water or a buffer solution, stirring and mixing to dissolve the hyaluronic acid, and then further combining a salt to form hyaluronic acid particles.

[0070] In addition, if the buffer solution itself exhibits the aforementioned predetermined ionic strength due to the action of the salt contained in the buffer solution, the addition of the salt may be omitted.

[0071] In addition, regarding various materials such as hyaluronic acid, water, buffer solution, and optional ingredients that can be used in the method of preparing cosmetics, various materials in the aforementioned cosmetic items may be used. Here, when incorporating optional ingredients, such optional ingredients may be incorporated before they become hyaluronic acid particles; however, to avoid affecting particle formation, it is preferable to incorporate them after the hyaluronic acid particles have been prepared.

[0072] The amount of hyaluronic acid can be 0.005 mass% or more, 0.01 mass% or more, 0.05 mass% or more, 0.10 mass% or more, 0.15 mass% or more, 0.20 mass% or more, or 0.25 mass% or more with respect to the total amount of the cosmetic product, and can also be 1.0 mass% or less, 0.80 mass% or less, 0.60 mass% or less, 0.50 mass% or less, or 0.45 mass% or less.

[0073] Areas of Application for Cosmetics

[0074] The cosmetic composition of the present disclosure may be applied and used on any surface of the skin on any part of the body. For example, it may be appropriately applied to the skin surface of the face (lips, eye area, eyelids, cheeks, forehead, glabella, nose, etc.), ears, hands, arms, neck, legs, feet, chest, abdomen, back, etc. Here, the skin includes fingernails, etc., which are hardened nails resulting from changes in the keratin of the skin's epidermis.

[0075] Other Uses of Hyaluronic Acid Particles

[0076] The hyaluronic acid particles of the present disclosure may be used for purposes other than cosmetics, such as external skin preparations, pharmaceuticals, and quasi-pharmaceuticals.

[0077] Examples

[0078] The present invention will be described in more detail below with reference to test examples and embodiments, but the present invention is not limited thereto.

[0079] Test Examples 1–6

[0080] <Evaluation of Composition>

[0081] Various evaluations as shown below were performed on the compositions obtained by the manufacturing method described below, and the results are summarized in Tables 1 to 6 and Figures 1 to 6. In addition, "HA" in the tables and figures is intended to be hyaluronic acid.

[0082] (Evaluation of average particle diameter)

[0083] The average particle diameter of the hyaluronic acid particles in the composition was evaluated based on the Z average particle diameter by dynamic light scattering using a Zetasizer (manufactured by Malvern Panalytical Co., Ltd.) or a dynamic light scattering photometer DLS-8000 (manufactured by Otsuka Denshi Co., Ltd.).

[0084] (Evaluation of moisture content ratio)

[0085] After washing the inner side of the subject's upper arm with soap, the subject was subjected to environmental conditioning by spending 20 minutes in a constant temperature and humidity chamber at a temperature of 21±1℃ and a relative humidity of 45±5%. Subsequently, the moisture content on the skin surface of the washed inner side of the upper arm before the application of the composition, and the moisture content 20, 30, 60, and 120 minutes after applying one drop (2×2 cm²) of the composition to the skin surface, were measured using a Corneometer (trademark) CM825 (manufactured by Courage and Khazaka). From each obtained moisture content, the moisture content ratio was calculated using the following Equation 1:

[0086] Moisture content ratio = Moisture content after application of composition / Moisture content before application of composition … Equation 1

[0087] <Test Example 1: Influence of Ionic Strength>

[0088] In Test Example 1, the effect of ionic strength on the particle diameter of hyaluronic acid particles was examined. The results are shown in Table 1 and Figure 1.

[0089] (Method of preparing the composition)

[0090] Hyaluronic acid (manufactured by Shiseido Co., Ltd., BIO HIARO 12: weight average molecular weight 1.2 million) was added to ion-exchanged water at a content of 0.1 mass% and stirred and mixed with a vortex mixer to prepare composition A. After dissolving the hyaluronic acid, sodium chloride was added to each composition A, which was divided so that the ionic strength of the salt was 0.001, 0.003, 0.01, 0.02, 0.03, and 0.10, at concentrations of 0.01 M (mol / ℓ), 0.003 M, 0.01 M, 0.02 M, 0.03 M, and 0.10 M, and stirred and mixed with a vortex mixer to prepare hyaluronic acid particle-containing compositions. Here, in the case of sodium chloride composed of monovalent cations and monovalent anions, the concentration of sodium chloride and the ionic strength values ​​are the same.

[0091]

[0092] (result)

[0093] As is evident from the results in Table 1 and Figure 1, it was confirmed that nanometer-order hyaluronic acid particles were obtained by adding salt. In addition, as the amount of salt added increased, i.e., as the ionic strength increased, the particle diameter of the hyaluronic acid particles showed a tendency to decrease, and in particular, it was confirmed that hyaluronic acid particles of 100 nm or less were obtained when the ionic strength was 0.03 or higher.

[0094] <Test Example 2: Effects of Hyaluronic Acid Concentration and Ionic Strength>

[0095] In Test Example 2, the influence of the concentration of hyaluronic acid and ionic strength during the preparation of the composition on the particle diameter of hyaluronic acid particles was examined. The results are shown in Table 2 and Figure 2.

[0096] (Method of preparing the composition)

[0097] Each hyaluronic acid particle-containing composition was prepared in the same manner as in Test Example 1, except that the concentration of hyaluronic acid at the time of composition preparation was set to 0.01 mass%, 0.1 mass%, 0.2 mass%, 0.3 mass%, 0.4 mass%, and 0.5 mass%, and sodium chloride was added so that the ionic strength was in the ratio listed in Table 2.

[0098]

[0099] (result)

[0100] As is evident from the results in Table 2 and Figure 2, it was confirmed that nanometer-order hyaluronic acid particles were obtained by adding salt even as the concentration of hyaluronic acid increased.

[0101] <Test Example 3: Effect of Ionic Strength at Hyaluronic Acid Concentration of 0.4–0.5 Mass%>

[0102] In Test Example 3, the effect of ionic strength on hyaluronic acid particles was examined when the concentration of hyaluronic acid at the time of composition preparation was 0.4 to 0.5 mass%. The results are shown in Table 3 and Figure 3.

[0103] (Method of preparing the composition)

[0104] A hyaluronic acid particle-containing composition was prepared in the same manner as in Test Example 1, except that the concentration of hyaluronic acid was set to 0.4 mass% and 0.5 mass%, and sodium chloride was added so that the ionic strength was in the ratio listed in Table 3.

[0105]

[0106] (result)

[0107] As is evident from the results in Table 3 and Figure 3, it was confirmed that hyaluronic acid particles of 200 nm or less were obtained when the ionic strength was 0.05 or higher in both cases where the hyaluronic acid concentration was 0.4 mass% and 0.5 mass%. In particular, when the hyaluronic acid concentration was 0.4 mass%, it was confirmed that hyaluronic acid particles of 100 nm or less were obtained when the ionic strength was in the range of 0.20 to 1.0.

[0108] <Test Example 4: Effect of Hyaluronic Acid Particle Diameter on Moisturizing Properties>

[0109] In Test Example 4, the effect of the particle diameter of hyaluronic acid particles on moisturizing properties was examined. The results are shown in Table 4 and Figure 4. Here, it can be said that the moisturizing performance is improved compared to the state before application of the composition as the moisture content ratio increases above 1. The moisture content ratio is preferably 1.25 or higher, more preferably 1.30 or higher, and particularly preferably 1.35 or higher.

[0110] (Method of preparing the composition)

[0111] Each hyaluronic acid particle-containing composition was prepared in the same manner as Test Example 1, except that the concentration of hyaluronic acid was 0.4 mass% and sodium chloride was added so that the ionic strength was in the ratio listed in Table 4. Here, hyaluronic acid molecules in the composition with an ionic strength of 0, to which sodium chloride was not added, are thought to diffuse into a thread-like shape and not take the form of particles, so they are labeled as "non-particles" in the table and drawings.

[0112]

[0113] (result)

[0114] As is evident from the results in Table 4 and Figure 4, in the case of compositions containing non-particulate hyaluronic acid and compositions containing hyaluronic acid particles with an average particle diameter of 294 nm or more, moisturizing performance temporarily increases immediately after the composition is applied to the skin, but the moisturizing performance decreases after only about 30 minutes and shows only moisturizing performance similar to that of the state without the composition being applied. This is thought to be because the hyaluronic acid in these compositions does not penetrate into the skin.

[0115] Meanwhile, in the case of a composition containing hyaluronic acid particles with an average particle diameter of 84 nm, it was confirmed that excellent moisturizing performance is immediately exhibited when the composition is applied to the skin, and that such moisturizing performance can be maintained over a long period. It is believed that the immediate and sustained effects of this moisturizing performance are due to the fact that the hyaluronic acid particles are in the form of ultrafine particles of 200 nm or less that are easy to penetrate into the skin, and that the proportion of hyaluronic acid contained in the particles is high.

[0116] <Test Example 5: Effect of Sodium Citrate on the Particle Diameter of Hyaluronic Acid Particles>

[0117] In Test Example 5, the effect of sodium citrate on the particle diameter of hyaluronic acid particles was examined. The results are shown in Table 5 and Figure 5.

[0118] (Method of preparing the composition)

[0119] Hyaluronic acid (manufactured by Shiseido Co., Ltd., Bio Hyalo 12: weight average molecular weight 1.2 million) was added to a citric acid buffer (manufactured by Fujifilm Wako Junyaku Co., Ltd.: pH 6.5, ionic strength 0.006) at a content of 0.1 mass% and mixed by stirring with a vortex mixer to prepare composition B. After dissolving the hyaluronic acid, sodium citrate was added to each of the compositions B, which were taken such that the ionic strength of the salt was 0.03, 0.06, and 0.30, and mixed by stirring with a vortex mixer to prepare hyaluronic acid particle-containing compositions. Here, the concentration of sodium citrate at an ionic strength of 0.03 was 0.005 M, the concentration of sodium citrate at an ionic strength of 0.06 was 0.010 M, and the concentration of sodium citrate at an ionic strength of 0.30 was 0.050 M.

[0120]

[0121] (result)

[0122] As is evident from the results in Table 5 and Figure 5, it was confirmed that hyaluronic acid particles of 200 nm or less could be obtained even with salts other than sodium chloride.

[0123] <Test Example 6: Effect of Use of Hydrogen Bonding Inhibiting Additive on Particle Diameter of Hyaluronic Acid Particles>

[0124] From Test Example 6, the effect of the use of urea, an additive that inhibits hydrogen bonding, on the particle diameter of hyaluronic acid particles was examined. The results are shown in Table 6 and Figure 6.

[0125] (Example 1)

[0126] Hyaluronic acid (Bio Hyalo 12, manufactured by Shiseido Co., Ltd.: weight average molecular weight 1.2 million) was added to ion-exchanged water at a content of 0.1 mass% and mixed by stirring with a vortex mixer to prepare composition C. After dissolving the hyaluronic acid, sodium chloride was added to composition C at a concentration of 0.10 M so that the ionic strength of the salt became 0.10, and mixed by stirring with a vortex mixer to prepare a composition containing hyaluronic acid particles.

[0127] (Example 2)

[0128] Hyaluronic acid (Bio Hyalo 12, manufactured by Shiseido Corporation: weight average molecular weight 1.2 million) was added to an isotonic phosphate buffer (manufactured by Takara Bio Corporation: pH 7.4, ionic strength 0.154) at a content of 0.1 mass%, and a hyaluronic acid particle-containing composition was prepared by stirring and mixing with a vortex mixer.

[0129] (Comparative Example 1)

[0130] The composition of Comparative Example 1 was prepared by adding 10 mass% of urea to the entire amount of the hyaluronic acid particle-containing composition of Example 1.

[0131] (Comparative Example 2)

[0132] The composition of Comparative Example 2 was prepared by adding 10 mass% of urea to the entire amount of the hyaluronic acid particle-containing composition of Example 2.

[0133]

[0134] (result)

[0135] From the results of Table 6 and Figure 6, it was confirmed that when an element that exerts a hydrogen bond-cleaving effect is added to the composition, the particle diameter of the hyaluronic acid particles increases significantly. As is evident from these results, the hyaluronic acid particles prepared by the method of the present disclosure are thought to be particles formed by hydrogen bonding, rather than particles obtained by cross-linking that is not affected by the element, because the particle diameter of the hyaluronic acid particles prepared by the method of the present disclosure varies depending on the inclusion of the element that cleaves hydrogen bonds.

[0136] Examples of Cosmetic Prescriptions

[0137] Below are examples of formulations in which hyaluronic acid particles prepared by the method of the present disclosure are used as a cosmetic, but these examples are not limited thereto. Furthermore, when the cosmetic described in the following examples is applied to the skin, excellent moisturizing performance can be exhibited over a long period of time.

[0138] <Prescription Example 1: Cosmetics>

[0139] (ingredient) (mass%)

[0140] Ion exchange water Remaining

[0141] Hyaluronic acid 0.1

[0142] sodium chloride 0.1

[0143] spices Appropriate amount

[0144] (Method of manufacturing cosmetics)

[0145] Hyaluronic acid was added to ion-exchanged water and dissolved by stirring with a vortex mixer. Subsequently, sodium chloride was added to the prepared aqueous hyaluronic acid solution and stirred with a vortex mixer to prepare hyaluronic acid particles, after which a fragrance was added to prepare a cosmetic product.

Claims

Claim 1 A cosmetic composition comprising an aqueous medium and hyaluronic acid particles dispersed in the aqueous medium, wherein the average particle diameter of the hyaluronic acid particles is 200 nm or less. Claim 2 A cosmetic composition according to claim 1, wherein the weight average molecular weight of the hyaluronic acid is 10,000,000 or less. Claim 3 A cosmetic composition comprising at least one salt selected from inorganic salts and organic salts, in accordance with claim 1 or 2. Claim 4 A cosmetic product according to paragraph 3, wherein the ionic strength of the salt is 0.01 or higher. Claim 5 A cosmetic composition according to any one of claims 1 to 4, wherein the content of the hyaluronic acid particles is 0.005 mass% or more. Claim 6 A cosmetic composition according to any one of claims 1 to 5, wherein the content of an ionic compound, glycols, ethanol, and urea is each 15 mass% or less. Claim 7 A cosmetic applied to the skin in any one of paragraphs 1 to 6. Claim 8 A method for preparing a cosmetic composition according to any one of claims 1 to 7, wherein a salt is mixed with water or a buffer solution, and then hyaluronic acid is further mixed to prepare hyaluronic acid particles. Claim 9 A method for preparing a cosmetic according to any one of claims 1 to 7, wherein hyaluronic acid is dissolved by mixing it with water or a buffer solution, and then a salt is further mixed to prepare hyaluronic acid particles.